Analysis of the life style of chronic renal patients doing hemodialysis - Kirchner, Rosane Maria; Figueira Machado, Renata; Löbler, Lisiane; Miladi Fernandes Stumm, Eniva (O Mundo da Saúde, 2011)
Chronic Renal Insufficiency (CRI) is a disease with a high morbidity and mortality rate, characterized by renal damage or reduction of the renal function for three or more months. This research aimed to evaluate the life style of chronic renal patients in hemodialytic treatment. The present work is a quantitative, descriptive, transversal research developed with 32 patients who have hemodialysis in a center of dialysis of a city of the west part of State Rio Grande do Sul. Observing all ethical rules, the project was approved by the Ethics Committee (Parecer Consubstanciado No. 02780243000-09). For data collection, an instrument was used that have data on the life style of patients, and data were analyzed with software SPSS and descriptive statistics. It was observed that 65.6% of the participants of the research did not practice any physical activity; 46.9% received aid to carry through some dally activities; 65.6% did not have leisure activities; 12.6% were smokers; the consumption of salt, greasy candies and foods was moderate; 93.8% had affirmed not to drink alcoholic beverages or to drink only small amounts. The relationship of most patients with people such as relatives and friends is perceived and evaluated as good. The researched patients may modify their life habits and consequently contribute to the improvement of their conditions of health and life.